Penerapan Evidance Based Nursing ROM Pasif untuk Meningkatkan Kekuatan Otot pada Pasien Post Operasi Fraktur Femur - Saidah Saniyah; Erida Fadila; Dwiyanti Purbasari (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2026)
Background: Patients undergoing Open Reduction and Internal Fixation (ORIF) for femoral fractures often experience impaired physical mobility due to pain, immobilization, and decreased muscle strength. Passive Range of Motion (ROM) exercises are one of the nursing interventions that can help improve muscle strength and accelerate the recovery of extremity function. Objective: To describe the implementation of passive ROM exercises in improving muscle strength among post-ORIF femoral fracture patients. Methods: This study used a descriptive case study design involving three post-ORIF femoral fracture patients with impaired physical mobility. Passive ROM exercises were administered for 3×24 hours and evaluated using Manual Muscle Testing (MMT). Results: All patients showed an improvement in muscle strength from an average score of 2/5 to 3/5. In addition, joint range of motion increased, pain decreased, and mobility gradually improved. Implications: Passive ROM exercises can be used as a nursing intervention to improve muscle strength and physical mobility while supporting the rehabilitation process in post-operative femoral fracture patients.